Athermal influence of high-density pulsed electric current on the mechanical properties and microstructure of AZ31 alloy during rolling - Weiping Huang; Binshan Wang; Lu Wang; Di Su; Qiang Zhang; Jianfeng Fan; Weiguo Li; Hongbiao Dong (Journal of Materials Research and Technology)
This study investigated the influence of electric pulse rolling (ER) on dynamic recrystallization (DRX) behavior, microstructure and mechanical properties of AZ31 magnesium alloy. By fixing a high frequency and low pulse width, the maximum temperature rise introduced by the electric pulse is only 7.1 °C, which infers that the impact of Joule heating from the pulse current was minimized. However, the DRX fractions of the ER sheets were increased while their basal texture strengths were decreased compared to the conventional hot rolled (WR) sheets. Accordingly, the mechanical properties of the ER sheets improved with increasing pulse voltages, and the yield stress (YS), ultimate tensile strength (UTS) and elongation of the ER-90V sample reached 290 MPa, 361 MPa and 8.28 %, respectively. The mechanisms of microstructure transformation and the enhanced mechanical properties were analyzed based on the athermal effect of the electric pulse, which promotes the grain refinement by accelerating dislocation movement and increasing the recrystallization nucleation rate.